2018
DOI: 10.1016/j.molcel.2018.08.042
|View full text |Cite
|
Sign up to set email alerts
|

The Chromatin Reader ZMYND8 Regulates Igh Enhancers to Promote Immunoglobulin Class Switch Recombination

Abstract: SummaryClass switch recombination (CSR) is a DNA recombination reaction that diversifies the effector component of antibody responses. CSR is initiated by activation-induced cytidine deaminase (AID), which targets transcriptionally active immunoglobulin heavy chain (Igh) switch donor and acceptor DNA. The 3′ Igh super-enhancer, 3′ regulatory region (3′RR), is essential for acceptor region transcription, but how this function is regulated is unknown. Here, we identify the chromatin reader ZMYND8 as an essential… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
58
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
4
3
1

Relationship

3
5

Authors

Journals

citations
Cited by 41 publications
(68 citation statements)
references
References 98 publications
6
58
0
1
Order By: Relevance
“…Whether both transcriptional and post-transcriptional activities of the NuRD complex contribute to regulate p53 levels in activated B cells is not clear at present, but both appear to be mediated via NuRD-dependent function of CHD4. In this regard, another NuRD complex associated factor ZMNYD8 has recently been shown to influence CSR by regulating the activity of the 3 ’ Igh super-enhancer ( Delgado-Benito et al, 2018 ). Additionally, on the basis of the ability of the NuRD complex to regulate acetylation of p53 protein, it is possible that it could also impact PTMs of AID and other factors that participate in different stages of B cell development and differentiation.…”
Section: Discussionmentioning
confidence: 99%
“…Whether both transcriptional and post-transcriptional activities of the NuRD complex contribute to regulate p53 levels in activated B cells is not clear at present, but both appear to be mediated via NuRD-dependent function of CHD4. In this regard, another NuRD complex associated factor ZMNYD8 has recently been shown to influence CSR by regulating the activity of the 3 ’ Igh super-enhancer ( Delgado-Benito et al, 2018 ). Additionally, on the basis of the ability of the NuRD complex to regulate acetylation of p53 protein, it is possible that it could also impact PTMs of AID and other factors that participate in different stages of B cell development and differentiation.…”
Section: Discussionmentioning
confidence: 99%
“…Upon cytokine stimulation, CH12 cells express AID and undergo CSR to IgA with high efficiency (Nakamura et al, 1996). CRISPR-Cas9-mediated deletion of factors required for CSR reduces the efficiency of isotype switching in this cell line (Delgado-Benito et al, 2018). Among all tested candidates, targeting of Pdap1 resulted in a considerable reduction of CSR (Fig.…”
Section: Resultsmentioning
confidence: 92%
“…Selected clones R1/R2 and P1/3 were validated at the level of genomic scar and protein expression. The sequences of the gRNAs used in these studies (this paper; Delgado-Benito et al, 2018) are listed in Table S2.…”
Section: Crispr-cas9 Gene Targetingmentioning
confidence: 99%
“…While initial studies identified mainly proteins whose recruitment to chromatin was mediated via interaction of PHD domains with H3K4me2 or H3K4me3 [107], there is evidence that certain PHD domains can also recognize lower-order methylation or even unmethylated lysines [108]. In fact, ZMYND8 has been identified as a PHD domain-containing chromatin factor at enhancers whose recruitment may be stabilized by the presence of unmethylated or monomethylated H3K4 [109][110][111]. Recent evidence suggests that H3K4me1 may also contribute to complex formation on chromatin through interaction with the PHD1-PHD2 domains of BAF45C, a member of the BAF chromatin remodelling complex [112].…”
Section: Histone Modifications and Enhancer Activation 41 H3k4me1mentioning
confidence: 99%